The Association Between Triglyceride-Glucose Index as a Marker of Insulin Resistance and the Risk of Breast Cancer - Panigoro, Sonar Soni; Sutandyo, Noorwati; Witjaksono, Fiastuti; Siregar, Nurjati Chairani; Ramli, Ramadhan; Hariani, Ririn; Pangarsa, Eko Adhi; Prajoko, Yan Wisnu; Puruhita, Niken; Hamdani, William; Bayu, Dimas; Madjid, Mardiana; et al. (Frontiers in Endocrinology, 2021)
Background This study aims to evaluate the association between TyG index and breast cancer, and assessing the dose-response between TyG index and breast cancer. Method This was a multicenter case-control study conducted in six public referral hospitals in Indonesia. Cases are individuals aged 19 years or above who were diagnosed with breast cancer within one year of diagnosis, based on histopathology and immunohistochemistry. Controls were recruited from corresponding hospitals. TyG index was determined by the formula: ln (fasting TG [mg/dL] × fasting glucose [mg/dL]) Results There were 212 participants in the breast cancer group and 212 participants in the control group. TyG index was higher in patients with breast cancer (median 8.65 [7.38, 10.9] vs. 8.30 [7.09, 10.84], p<0.001). When compared to TyG quartile of Q1, Q4 was associated with an OR of 2.42 (1.77, 3.31), p<0.001, Q3 was associated with an OR of 1.53 (1.21, 1.93), p<0.001, Q2 was associated with an OR of 1.39 (1.12, 1.73), p=0.002 for the risk of breast cancer. The dose-response relationship was non-linear (p<0.001). On univariate analysis, smoking (OR 2.15 [1.44, 3.22], p<0.001), use of contraception (1.73 [1.15, 2.60], p=0.008), alcohol consumption (OR 2.04 [0.96, 4.35], p=0.064), and TyG Index >8.87 (OR 3.08 [1.93, 4.93], p<0.001) were associated with risk of breast cancer. independently associated with increased risk of breast cancer included smoking (OR 1.93 [1.23, 3.01], p=0.004), use of contraception (OR 1.59 [1.02, 2.48], p=0.039), and TyG Index >8.87 (OR 2.93 [1.72, 4.98], p<0.001) Conclusion TyG index was associated with breast cancer in a non-linear dose-response fashion